Cannabidiol as a Novel Candidate Alcohol Use Disorder Pharmacotherapy: A Systematic Review. (19th February 2019) - Turna, Jasmine; Syan, Sabrina K.; Frey, Benicio N.; Rush, Brian; Costello, Mary Jean; Weiss, Mark; MacKillop, James
Abstract : There is substantial interest in the therapeutic potential of cannabidiol (CBD), a nonpsychoactive cannabinoid found in plants of the genus Cannabis . The goal of the current systematic review was to characterize the existing literature on this topic and to evaluate the credibility of CBD as a candidate pharmacotherapy for alcohol use disorder (AUD). Using a comprehensive search strategy, 303 unique potential articles were identified and 12 ultimately met criteria for inclusion (8 using rodent models, 3 using healthy adult volunteers, and 1 using cell culture). In both rodent and cell culture models, CBD was found to exert a neuroprotective effect against adverse alcohol consequences on the hippocampus. In rodent models, CBD was found to attenuate alcohol‐induced hepatotoxicity, specifically, alcohol‐induced steatosis. Finally, findings from preclinical rodent models also indicate that CBD attenuates cue‐elicited and stress‐elicited alcohol seeking, alcohol self‐administration, withdrawal‐induced convulsions, and impulsive discounting of delayed rewards. In human studies, CBD was well tolerated and did not interact with the subjective effects of alcohol. Collectively, given its favorable effects on alcohol‐related harms and addiction phenotypes in preclinical models, CBD appears to have promise as a candidate AUD pharmacotherapy. This is further bolstered by the absence of abuse liability and its general tolerability. A clear limitation to the literature is the paucity of human investigations. Human preclinical and clinical studies are needed to determine whether these positive effects in model systems substantively translate into clinically relevant outcomes. Abstract : There is burgeoning interest in cannabidiol (CBD), a nonpsychoactive constituent of cannabis, for many health conditions. This review critiqued the evidence in relation to alcohol use disorder (AUD). In studies using animal models, there was evidence that CBD has neuroprotective effects and reduces alcohol‐related liver harms, alcohol‐seeking behavior, impulsivity, and withdrawal symptoms. However, almost no studies examined CBD in relation to alcohol in humans. This figure presents candidate mechanisms by which CBD may be useful as a treatment for AUD.